2017
DOI: 10.1021/acs.organomet.7b00381
|View full text |Cite
|
Sign up to set email alerts
|

BArF3-Catalyzed Imine Hydroboration with Pinacolborane Not Requiring the Assistance of an Additional Lewis Base

Abstract: The rarely used boron Lewis acid tris [3,5-bis-(trifluoromethyl)phenyl]borane (BAr F 3 ) is found to be an excellent catalyst for metal-free hydroboration of imines. In the presence of 1.0 mol % of BAr F 3 , several ketimines and aldimines undergo hydroboration with pinacolborane (HBpin) at room temperature without the aid of an external Lewis base. BAr F 3 is more reactive than other Lewis acidic boranes, including the often-used tris(pentafluorophenyl)borane (B(C 6 F 5 ) 3 ). The steric hindrance imparted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 34 publications
4
65
0
Order By: Relevance
“…As expected, hydroboration at ambient temperature using 1.5 equiv of H‐Bpin with respect to ketimine was not successful. However, hydroboration was realized when reaction was performed at higher temperature of 60 °C (Scheme ) although effectiveness is much lower than previously reported catalyzed reactions and the corresponding amines were obtained in moderate to good yields after hydrolysis. Reduction of N ‐(α‐methylbenzylidene)aniline 4 a followed by hydrolysis yielded the N ‐(α‐methylbenzyl)aniline 6 a in good yield of 70 %.…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…As expected, hydroboration at ambient temperature using 1.5 equiv of H‐Bpin with respect to ketimine was not successful. However, hydroboration was realized when reaction was performed at higher temperature of 60 °C (Scheme ) although effectiveness is much lower than previously reported catalyzed reactions and the corresponding amines were obtained in moderate to good yields after hydrolysis. Reduction of N ‐(α‐methylbenzylidene)aniline 4 a followed by hydrolysis yielded the N ‐(α‐methylbenzyl)aniline 6 a in good yield of 70 %.…”
Section: Methodsmentioning
confidence: 78%
“…In 2012, Crudden and co‐workers reported an efficient FLP system generated from DABCO, pinacolborane and B(C 6 F 5 ) 3 . After this report, various protocols utilizing Lewis acid (mainly boron based), Br ø nsted acid, and recently, diazaphospholene‐based phosphorus hydride as catalyst have been reported (Scheme ) . However, hydroboration of imines with most of these catalysts demands either elevated reaction temperature or longer reaction duration along with high catalyst loading .…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Classically, there has been focus on the use of precious metal catalysts for this transformation, [4][5][6] but recently there has been a surge of interest in using more abundant, non-toxic, and cheaper alternatives such as early transition metals and main group elements. 1,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Recent work has shown that Lewis acidic boranes and borocations can act as efficient catalysts for this process (Fig. 1).…”
mentioning
confidence: 99%
“…1). [11][12][13][14] For example, Oestreich explored the use of tris [3,5-bis(trifluoromethyl)phenyl]borane (BAr F 3 ), whilst we have focused on the use of tris(2,4,6-trifluorophenyl)borane (B(2,4,6-Ar F ) 3 ), 11,12 with both catalysts proving to be more active than the archetypal tris(pentafluorophenyl)borane (B(C 6 F 5 ) 3 ). The aforementioned borane catalysts work efficiently but are sometimes hindered by lengthy reaction times and limited substrate scope, particularly in the case of ketones, alkenes and alkynes.…”
mentioning
confidence: 99%
See 1 more Smart Citation